THE APPLICATION OF STAD COOPERATIVE LEARNING MODEL TYPE TO MASTERY OF STUDENTS CONCEPTS - Desmalina Sagita; Pramudiyanti Pramudiyanti; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The problems in the learning process at Junior High School 13 Bandar Lampung is still dominating the teacher in the classroom. This results in low student concept mastery. cooperative learning model of STAD type to enable the students to learn so that students can increase mastery of concepts. The purpose of this study was to determine (1) the use of cooperative learning model type STAD significantly affect students mastery of concepts in the subject matter of the respiratory system in humans. (2) the average students mastery concepts using cooperative learning model STAD type of subject matter in the human respiratory system is higher.  (3) students learning activities using cooperative learning model STAD type of subject matter in the human respiratory system is higher. The sample in this study was VIIIC and VIIIE graders who were randomly selected by cluster random sampling technique. The results showed an average N-gain of the experiment class is 50.74 higher than the control class is 32.05. Test t1 to N-gains obtained on the tcount(-5.224) ttable(2.000) so that H0 is rejected. That is an average of N-gain in the experimental class significantly different from the average N-gain the control class. Then t2 test results show that tcount(19.343) ttable(2.042) so that H0 is rejected. That is an average of N-gain in the experimental class higher than the average N-gain the control class, so that students mastery of concepts can be expressed on the subject matter of the respiratory system in humans using cooperative learning model of STAD type is higher than the model of learning directly. Keywords: STAD, students mastery of concepts, the respiratory system.